2016
DOI: 10.1148/radiol.2016152444
|View full text |Cite
|
Sign up to set email alerts
|

Focused Ultrasound Enhances Central Nervous System Delivery of Bevacizumab for Malignant Glioma Treatment

Abstract: Purpose To demonstrate that magnetic resonance (MR) imaging-monitored transcranial focused ultrasound can enhance the delivery of the antiangiogenic monoclonal antibody bevacizumab into the central nervous system (CNS) for glioblastoma multiforme (GBM) treatment. Materials and Methods All animal experiments were approved by the animal committee and adhered to experimental animal care guidelines. Transcranial focused ultrasound exposure in the presence of microbubbles was used to open the blood-brain barrier (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(76 citation statements)
references
References 27 publications
2
74
0
Order By: Relevance
“…2B, mean ± standard deviation), which is lower than the monovalent affinity for the full-length IgG (K d = 0.35 nM) generated using the same variable regions (27). Even though scFv constructs are highly advantageous for imaging (37) and delivery (38)(39)(40), a 5 to 15-fold reduction in affinity upon conversion of IgG to scFv had been reported (38,41), potentially due to higher stability and functional concentration of full IgGs. To confirm that the yeast displayed scFv was properly folded, we generated alanine point mutations in the CDR residues that interacted with the phosphoepitope (Supp.…”
Section: Yeast Surface Display Of a Phospho-tau-specific Scfvmentioning
confidence: 85%
See 1 more Smart Citation
“…2B, mean ± standard deviation), which is lower than the monovalent affinity for the full-length IgG (K d = 0.35 nM) generated using the same variable regions (27). Even though scFv constructs are highly advantageous for imaging (37) and delivery (38)(39)(40), a 5 to 15-fold reduction in affinity upon conversion of IgG to scFv had been reported (38,41), potentially due to higher stability and functional concentration of full IgGs. To confirm that the yeast displayed scFv was properly folded, we generated alanine point mutations in the CDR residues that interacted with the phosphoepitope (Supp.…”
Section: Yeast Surface Display Of a Phospho-tau-specific Scfvmentioning
confidence: 85%
“…This has led to significant enhancement in processes that rely on diffusion, such as tissue penetration. For example, when the blood-brain barrier was transiently opened through focused ultrasound, scFvs showed 5-to 57-fold higher uptake into the central nervous system compared to IgGs (40). In a mouse model of tauopathy, intravenously injected scFvs were detected in the brain tissue in significantly higher levels compared to that of IgGs (37).…”
Section: Discussionmentioning
confidence: 99%
“…Delivery of doxorubicin to a brainstem was also recently shown to be feasible and safe for animals after histological and behavioral tests (50). Other chemotherapies investigated in conjunction with MRgFUS BBB opening in small (e.g., rat, rabbit) to large (e.g., nonhuman primates) animals include paclitaxel (60), methotrexate (61, 62), doxorubicin (50, 63, 64), cisplatin (65), bevacizumab (66), and carmustine (67) (Table 1). …”
Section: Chemotherapiesmentioning
confidence: 99%
“…This concept has been explored using multiple chemotherapeutics including doxorubicin (glioma), nitrosurea agents (glioma), bevacizumamab (glioma), and trastuzumab (breast metastasis). [14][15][16] These studies have demonstrated variable degrees of drug penetrance and tumoral killing. Currently, clinical trials (NCT02343991) are being conducted to evaluate the safety of MRFUS to transiently break down the BBB for delivery of intracranial doxorubicin.…”
Section: Applicationsmentioning
confidence: 99%